3D porous flower-like heterostructure of Fe doped Ni2P nanoparticles anchored on Al2O3 nanosheets as an ultrastable high-efficiency electrocatalyst. (20th July 2020) - Xu, Jing; Liu, Zhiyu; Wei, Zhengnan; Zhang, Shuying; Guo, Chaozhong; He, Mengyuan
Abstract: Water splitting is a vital candidate to efficiently prepare the green energy resource of hydrogen and solve the problem of energy shortage. Herein, this work firstly study a unique composite of 3D porous flower-like heterostructure of Fe doped Ni2 P nanoparticles anchored on Al2 O3 nanosheets, which exhibits excellent electrochemical performance for hydrogen evolution reaction (HER) in all-PH medium. In this research, the doped Fe element can tune the electronic structure of Ni2 P, which can remarkably improve the electrochemical activity. Besides, this unique 3D porous flower-like heterostructure possesses large specific surface area, which can expose a large number of active sites so as to further enhance the electrochemical property. Moreover, the Al2 O3 coating can further ensure the structure stability. The Ni1.4 (Fe0.6 )P@Al2 O3 displays splendid catalytic activity for HER with low overpotential of 53 mV and outstanding electrochemical durability of less than 3% increase in overpotential for 500 h at the constant density of 10 mA cm −2 . Graphical abstract: We firstly report novel 3D porous flower-like Ni1.4 (Fe0.6 )P@Al2 O3 heterostructure, which exhibits high-efficiency HER activities in all-PH medium. Image 1